Evidências científicas sobre violência contra a pessoa idosa no domicílio em tempos de pandemia da Covid-19 - Araújo, Marcella Campos de (Brasil, 2024)
Objective: Analyze the scientific evidence on violence against the elderly in the family context in times of the COVID-19 pandemic. Method: This is an integrative literature review, which included searches in the online databases and virtual library virtual Bdenf, SciELO, Lilacs, WOS, Medline, Cinahl, Science Direct and Scopus, in the period from 2019 to 2022, with the descriptors controlled by DeCS and MeSH. Results: The types of violence against the elderly in the family context during the covid-19 pandemic detected were financial abuse, neglect, abandonment, psychological abuse and physical abuse, with the last two standing out in relation to the others. The most relevant aggressors were children or spouses of children. Final considerations: The review showed the types of violence against the elderly, which were financial abuse, neglect, abandonment, psychological abuse and physical abuse, with the most frequent aggressors being the children of the elderly